Renal biomarkers reflect overall hypertensive organ damage: "one organ to rule them all". (14th October 2021) - Terentes-Printzios, D; Aznaouridis, K; Ioakeimidis, N; Gardikioti, V; Xaplanteris, P; Georgakopoulos, C; Dima, I; Oikonomou, D; Tsioufis, K; Vlachopoulos, C
Abstract: Background/Introduction: Hypertension is associated with higher cardiovascular risk as well as several markers of subclinical target organ damage (TOD). Albumin to creatinine ratio (ACR) in urine has been recognized as an independent risk factor for cardiovascular events. Purpose: We hypothesized that there is a relationship between ACR and markers of TOD in never-treated hypertensives. Methods: We enrolled 924 consecutive essential hypertensives (mean age 53±12 years, 486 males) without known cardiovascular disease (CVD). Markers of subclinical TOD [left ventricular mass index (LVMI), pulse wave velocity (PWV), ankle-brachial index (ABI) and estimated glomerular filtration rate (eGFR)] were evaluated in all patients. LVMI was assessed echocardiographically using the Devereux formula. Carotid-femoral PWV was estimated with the Complior device. eGFR was calculated by the Cockcroft-Gault formula. ABI was calculated by dividing the highest ankle systolic blood pressure by the highest brachial systolic blood pressure. Results: ACR exhibited significant association with LVMI (r=0.277, p<0.001, Figure), PWV (r=0.277, p<0.001) ABI (r=−0.078, p=0.018) and eGFR (r=−0.100, p=0.002). In further analysis, ACR was associated with TOD as suggested by the 2018 European Guidelines for Hypertension [left ventricular hypertrophy (LVMI>115 g/m 2 in men and >95 g/m 2 in women), increased PWV (PWV>10m/s), decreased ABI (ABI<0.9) and decreased renal function (eGFR<60ml/min)]. Specifically, ACR exhibited significant association with the number of TOD and this association was independent of age and gender (p<0.05). Conclusions: Our findings support the close relationship between ACR and TOD in hypertension, as well as, the predictive ability of ACR for TOD. FUNDunding Acknowledgement: Type of funding sources: None.